OPINI PUBLIK PELANGGAN TENTANG KOMUNIKASI NONVERBAL DALAM PENINGKATAN HUNIAN KAMAR DI HOTEL GARUDA PLAZA MEDAN - Nina Siti Salmaniah Siregar Hafiza Novenda (PERSPEKTIF, 2016)
The research wants to observe public opinion about women who work in hotel affairs. The problem about working in hotel is the working hour, sometimes in day time, but also night time. The condition make negative perception about working women in hotel affairs. This is descriptive analysis research. The result shows that most people have positive response about working women in hotel affairs because it increase family income.